THE INFLUENCE OF MOBILE PHONEâS FORMS IN THE USER PERCEPTION - Suteja, The Jaya; Tedjohartoko, Stephany (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
Not all types of mobile phone are successful in entering the market because some types of theÂ mobile phone have a negative perception of user. Therefore, it is important to understand the influence ofÂ mobile phoneâs characteristics in the local user perception. This research investigates the influence ofÂ QWERTY mobile phoneâs forms in the perception of Indonesian user. First, some alternatives of mobileÂ phoneâs form are developed based on a certain number of mobile phoneâs models. At the second stage, someÂ word pairs as design attributes of the mobile phone are chosen to represent the user perception of mobileÂ phone. At the final stage, a survey is conducted to investigate the influence of the developed form alternativesÂ to the user perception. Based on the research, users perceive mobile phoneâs form with curved top andÂ straight bottom shapes and mobile phoneâs form with slider and antenna as the most negative form.Â Meanwhile, mobile phoneâs form with curved top and bottom shapes and mobile phoneâs form without sliderÂ and antenna are perceived by the user as the most positive form.